1997
DOI: 10.1074/jbc.272.45.28202
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Precursor Interleukin (IL)-1α, but Not Mature IL-1α, Is Able to Regulate Human Endothelial Cell Migration in Vitro

Abstract: The human umbilical vein endothelial cell (HUVEC) has a finite lifespan in vitro, and senescent HUVEC contain elevated levels of the negative growth regulator interleukin (IL)-1␣. IL-1␣ is translated as a signal peptide sequence-less cytosolic 31-kDa precursor (IL-1␣ p), which undergoes proteolytic activation to release the mature carboxyl terminus 17-kDa protein (IL-1␣ m). Both the IL-1␣ p and IL-1␣ m proteins are biologically active as exogenous cytokines. Interestingly, only IL-1␣ p contains a nuclear local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…The original vector contains Myc and His tags downstream of the cloned cDNA, therefore, all the IL-1␣ proteins were expressed as double tagged chimeras with N-terminal FLAG and C-terminal Myc and His tags. Fragments encoding human deletion mutants IL-1NTP-VVATN (internal deletion aa 78 -87), IL-1NTP-EDSSS (terminal deletion aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and IL-1NTP-ITDDD (terminal deletion aa 96 -111) were amplified and cloned into BamHI and XhoI sites of modified pcDNA4/TO/MycHis (see above) vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original vector contains Myc and His tags downstream of the cloned cDNA, therefore, all the IL-1␣ proteins were expressed as double tagged chimeras with N-terminal FLAG and C-terminal Myc and His tags. Fragments encoding human deletion mutants IL-1NTP-VVATN (internal deletion aa 78 -87), IL-1NTP-EDSSS (terminal deletion aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and IL-1NTP-ITDDD (terminal deletion aa 96 -111) were amplified and cloned into BamHI and XhoI sites of modified pcDNA4/TO/MycHis (see above) vector.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, overexpressed intracellular IL-1␣ precursor (pre-IL-1␣), but not IL-1MAT, was able to inhibit cell growth and to induce the expression of the plasminogen activator inhibitor-1 and collagenase genes (9,10). Pre-IL-1␣ was shown to stimulate proliferation of smooth muscle cells (11) and to regulate the migration and the lifespan of endothelial cells (12,13). Thus, various effects of pre-IL-1␣ are found to be dependent on the presence of the acidic IL-1NTP fragment with the predicted pI 5.1.…”
mentioning
confidence: 99%
“…Since these studies suggested that TTM can repress the transcriptional activation of NF-κB, and NF-κB lies downstream of IL-1 receptor signaling (Baldwin, 1996), it appeared possible that TTM functions as a repressor of nonclassical IL-1α export. Both FGF1 and IL-1 play a proangiogenic role in vivo (Friesel and Maciag, 1999;Voronov et al, 2003) although, in vitro, FGF1 stimulates proliferation and migration of endothelial cells (Maciag et al, 1979;McMahon et al, 1997), whereas IL-1α inhibits both of these activities ). It appears that the regulation of angiogenesis and inflammation involves a coordination of nonclassical FGF1 and IL-1α release.…”
Section: Potential Role Of Detergent-like Properties and The Molten Gmentioning
confidence: 99%
“…As the transgene includes a nuclear localization sequence (aa 79 -86) that has been shown to be important for IL-1␣ association with the plasma membrane (24), MA-IL-1 is expected to express in Tg mice and play an important role in the development of joint destruction. The present study investigated whether biologically active hIL-1␣ derived from the transgene appears on the surface of synoviocytes, and whether MA-IL-1 contributes to synovial proliferation and cartilage destruction in the development of arthritis in hIL-1␣ Tg mice.…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%